Nuclear scaffold: Three‐dimensional indigenous capsular bag support combined with IOL scaffold and capsular tension ring to prevent posterior capsule rupture in zonulopathy. Issue 12 (December 2019) - Parkash, Rohit Om; Mahajan, Shruti; Parkash, Tushya Om; Parkash, Tushar Om; Rai, Milan
Abstract : We describe a technique for performing phacoemulsification in eyes with zonular fiber dehiscence of less than 90 degrees using hard nuclear fragments as a scaffold. In conjunction with a capsular tension ring (CTR), hard nuclear fragments and the intraocular lens (IOL) are used as scaffolds during different steps of nuclear emulsification to prevent posterior capsule rupture and aggravation of zonulopathy. Devices such as capsular hooks, CTRs, and IOLs are used to support the capsular bag associated with zonulopathy. The mass of hard nuclear fragments provides support toward the anteroposterior and the horizontal planes, thereby providing 3‐dimensional capsular bag support. Symbol Online Video